2005
DOI: 10.1038/sj.gene.6364265
|View full text |Cite
|
Sign up to set email alerts
|

Haplotypes in the CTLA4 region are associated with coeliac disease in the Irish population

Abstract: Chromosomal region 2q33 encodes the immune regulatory genes, CTLA4, ICOS and CD28, which are involved in regulation of T-cell activity and has been studied as a candidate gene locus in autoimmune diseases, including coeliac disease (CD). We have investigated whether an association exists between this region and CD in the Irish population using a comprehensive analysis for genetic variation. Using a haplotype-tagging approach, this gene cluster was investigated for disease association in a case-control study co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 46 publications
0
22
0
2
Order By: Relevance
“…17), and one may question whether a global haplotype protective effect is conferred by 15-2-4 and related extended haplotypes, rather than by single polymorphisms such as CT60. For instance, a recent investigation of susceptibility to celiac disease concluded that an extended haplotype stretching over CD28, CTLA4, and ICOSp was significantly overrepresented in controls and presumably more protective than any one SNP (33). Interestingly, this haplotype partially overlaps with the 15-2-4 haplotype defined here.…”
Section: Discussionmentioning
confidence: 80%
“…17), and one may question whether a global haplotype protective effect is conferred by 15-2-4 and related extended haplotypes, rather than by single polymorphisms such as CT60. For instance, a recent investigation of susceptibility to celiac disease concluded that an extended haplotype stretching over CD28, CTLA4, and ICOSp was significantly overrepresented in controls and presumably more protective than any one SNP (33). Interestingly, this haplotype partially overlaps with the 15-2-4 haplotype defined here.…”
Section: Discussionmentioning
confidence: 80%
“…37 This allele is carried in our risk CTLA4-ICOSe1 haplotype groups 2 and 4, although it is also present in some protective haplotypes. In addition, a study from Ireland reported the protective effect of a C-A-A haplotype in CD; 38 this smaller haplotype occurs frequently in our risk CTLA4-ICOSe1 haplotype group 2 but also exists in the protective haplotype groups 1 and 3. Hence, our results perhaps explain the apparently contradictory results in earlier studies (Table 5c).…”
Section: Discussionmentioning
confidence: 90%
“…1B). Similarly, a recent study of the costimulatory locus in patients with celiac disease showed that extended haplotypes in the region demonstrated stronger association with disease susceptibility than individual SNPs (39).…”
Section: Resultsmentioning
confidence: 99%